Broadband fitting approach for the application of supercontinuum broadband laser absorption spectroscopy to combustion environments. (10th December 2015) - Blume, Niels Göran; Ebert, Volker; Dreizler, Andreas; Wagner, Steven
Abstract: In this work, a novel broadband fitting approach for quantitative in-flame measurements using supercontinuum broadband laser absorption spectroscopy (SCLAS) is presented. The application and verification of this approach in an atmospheric, laminar, non-premixed CH4 /air flame (Wolfhard–Parker burner, WHP) is discussed. The developed fitting scheme allows for an automatic recognition and fitting of a B-spline curve reference intensity for SCLAS broadband measurements while automatically removing the influence of absorption peaks. This approach improves the fitting residual locally (in between absorption lines) and globally by 23% and 13% respectively, while improving the in-flame SNR by a factor of 2. Additionally, the approach inherently improves the time–wavelength-correlation based on recorded in-flame measurements itself in combination with a theoretical spectrum of the analyte. These improvements have allowed for the recording of complete spatially resolved methane concentration profiles in the WHP burner. Comparison of the measured absolute mole fraction profile for methane with previously measured reference data shows excellent agreement in position, shape and absolute values. These improvements are a prerequisite for the application of SCLAS in high-pressure combustion systems.